Interfaith Dialogue from the Perspective of Quran and Sunnah: A Solution for Peacemaking & Interfaith Harmony in Pakistan (Al-Qamar, 2022)
It is evident that Inter-faith dialogue is a tremendous initiative towards achieving harmony and building peace in the Society. It is recognized in the Holy Qurna and Sunnah that all human beings are basically equal. Respect for human dignity is the fundamental principle of Islam. From the perspective of Quran and Sunnah it is emphasized that dialogue should be promoted between Muslims and Non-Muslims to achieve harmony among the individuals belonging to various nations. Dialogue is based on various factors including culture, civilization and other valued principles. Interfaith dialogue is a base where mutual tolerance, respect and love is promoted. This research focuses on interfaith dialogue from the perspective of Quran and Sunnah with particular focus on peace building and interfaith harmony in Pakistan. It presents point of views of various scholars on the concept of interfaith dialogue. It also highlights that Pakistan is making its efforts for achieving the objectives including creating the social awareness in the society regarding interfaith harmony. The study ends with the concept that interfaith dialogue must be encouraged at all levels for promoting interfaith harmony and peace in the society.